Substituting open educational resources for commercial curriculum materials: effects on student mathematics achievement in elementary schools. Issue 1 (2nd January 2019) - Hilton, John; Larsen, Ross; Wiley, David; Fischer, Lane
ABSTRACT: Open Educational Resources (OER) have the potential to replace commercial learning materials in education. An empirical examination of this potential was conducted, comparing the end-of-year mathematics test results of 12, 110 elementary school students clustered within 95 schools from five school districts in the state of Washington in the United States of America. Of this group, 6796 students used open learning materials, and 5314 used commercial educational resources. When three years of test scores were considered, there were no statistically significant differences in the exam scores of students who used open versus commercial curriculum materials. The lack of statistical significance may have practical significance, demonstrating that OER can replace conventional materials without impacting student performance, while potentially reducing costs and allowing for local modification.